The Phenomenon of Worldly Love in the Digital Age: Thematic Interpretation of Surah Al-Hadid Verse 20 - Siahaan, Laily Nazmi; Luthviyah Romziana (Medina-te : Jurnal Studi Islam, 2025)
In the digital era, people are increasingly following trends that can be seen from social media such as Instagram and TikTok. This phenomenon can have a negative impact on life. A person will continue to follow trends that ultimately lead to regret. The main purpose of this study is to analyze the phenomenon of worldly love in the digital era based on the perspective of QS. Al-Hadid Verse 20 and what the impact of the influence of worldly love is in the digital era. This study also provides solutions based on the Qur'an to help people understand and overcome the negative effects of digitalization on spiritual values. This study uses a qualitative method with a library research approach. The data collection technique is carried out thematically (maudhu'i), making QS. Al-Hadid Verse 20 the center of analysis to explore the meaning of the verse in the context of the digital era. The results of the study, the love of the world in Surah Al-Hadid verse 20 includes la'ibun (something that does not bear fruit), lahwun (something that distracts humans from things that are useful and beneficial to them), ziinah (jewelry such as magnificent clothing), tafakhur (being proud of one another with lineage and parents who have become bones that have been destroyed), and takatsurun fil amwaali wal awlaad (boasting of one another). And the manifestation of love of the world is manifested in the form of social media addiction (La'ib and Lahwun), the emergence of (FOMO) "Fear Of Missing Out" (Takatsur), Showing Off Wealth or Lifestyle on the Internet (Flexing) (Tafakhur). Therefore, the Qur'anic solution recommended by the author is tajdid intention, digital zuhud, digital da'wah based on the afterlife, and finally tawazun (balance between the world and the afterlife)